2014
DOI: 10.1111/mms.12096
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal helminth fauna of striped dolphins (Stenella coeruleoalba) in the western Mediterranean: No effects of host body length, age and sex

Abstract: The intestine of 52 (28 males and 24 females) striped dolphins (Stenella coeruleoalba) from western Mediterranean waters was examined for helminths. Animals were found stranded along the Spanish coasts during the morbillivirus epizootic in 1990. In accordance with observations from other pelagic tetrapods, including cetaceans from other geographical regions, the intestinal helminth community was depauperate. Four helminth species were found: three tetrabothriid cestodes, Tetrabothrius forsteri (prevalence: 96.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
1
7
1
Order By: Relevance
“…Overall, all parasite species identified in this study were already reported in previous studies both in dolphins living in the Mediterranean Sea and in other seas [ 12 , 20 , 21 , 22 , 23 ].…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Overall, all parasite species identified in this study were already reported in previous studies both in dolphins living in the Mediterranean Sea and in other seas [ 12 , 20 , 21 , 22 , 23 ].…”
Section: Resultssupporting
confidence: 80%
“…Among cestode species for which dolphins are the definitive hosts ( Table 1 , Figure 3 ), the species Tetrabothrium forsteri (7.69%, 2/26; Figure 3 B1,B2) and Strobilocephalus triangularis (7.69%, 2/26; Figure 3 C) were here identified only in striped dolphins, both with a prevalence of about 13% (2/15). This prevalence is lower than that previously reported [ 20 ]. Both species infect the intestine but, while S. triangularis may be responsible for granulomatous nodular lesions, T. forsteri is considered a low-pathogenic parasite [ 35 ].…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…Interestingly, two main groups of intestinal helminths that could be predicted for cetaceans worldwide, i.e., cestode species of Tetrabothrius and acanthocephalan species of Bolbosoma (see Aznar et al, 2001), are apparently scarce or absent in delphinids of Argentine waters. For example, T. (T.) forsteri which exhibits high specificity mainly for delphinids (Mateu et al, 2014;Fraija-Fernández et al, 2016), has never been reported in the local dolphin populations off the Argentine coast. It seems plausible that this tapeworm species may not be present in this region of the southwestern Atlantic Ocean.…”
Section: Parasite Diversity and Life-cyclementioning
confidence: 99%